SISTEM TRACKING DAN MONITORING MOBIL RENTAL MENGGUNAKAN SENSOR GPS BERBASIS NODEMCU ESP32 - Alfith, Alfith; Effendi, Asnal; Al, Al; Maulana, Rizki (Jurnal Teknologi dan Vokasi, 2024)
Obtained conditions in which the Neo6 GPS module can detect the Earth's coordinates in the form of latitudes and volumes as well as the speed of the vehicle's movement to its coordinates. The app knows where you are based on the coordinates, speed, and impact of the car. In addition, the app sends speed warning notifications. In addition, the application can detect the correct or incorrect username and password to protect the view form. In addition, for research on a straight road and at a constant speed, the accuracy of the equipment will be tested by collecting GPS speed data and actual speed data if there is a significant change in speed in a short period of time. With four vehicle collision detection positions, testing this system yields an accurate conditional value. If an accident occurs, it will be immediately sent to the application and sent to a vehicle crash site used, as well as to the firebase database.